Pengembangan Bahan Ajar Interaktif Berbasis Flipbook pada Mata Pelajaran Dokumen Berbasis Digital: Implikasi Bagi Pembelajaran di Era Society 5.0 - Saraswati, Narulita Diva; Karunia Illahi, Artika Iesa; Arif, Amirul; Hakim, Luqman (FKIP, Universitas Banten Jaya, 2025)
This study aims to develop effective teaching materials in the form of handouts and flipbooks to enhance students' understanding and engagement in learning. Utilizing the Research and Development (R&D) method based on the ADDIE model, the research involved analyzing students' needs, designing, developing, implementing, and evaluating the teaching materials. The findings indicate that handouts organized with clear material sequences and alignment between content and exercises significantly improve students' understanding, with 48% of students reporting that the material presented was clear and appropriate for their abilities. Additionally, the flipbook, designed with visually appealing layouts and systematic content presentation, effectively boosts student motivation and facilitates comprehension of key concepts. This research emphasizes the importance of innovation in developing teaching materials relevant to students' characteristics in the 5.0 era, thereby supporting optimal learning outcomes.